The Treuhand and the Treuhanderschaft from the perspective of the specialised combined parallel-comparable corpus - Gvelesiani, Irina (Comparative Legilinguistics, 2024)
Corpora-based analysis has become one of the major methodologies used in linguistics. However, it has not been widely applied in legalese studies. The paper makes an attempt to discuss the usefulness of the specialized combined parallel-comparable corpus while dealing with the legal language. The effectiveness is presented on the example of the Treuhand and the Treuhänderschaft. The research is based on the comparative analysis as well as the corpus-based analysis of the terms related to the Treuhand and the Treuhänderschaft presented in two varieties of German: Standard German spoken in Germany and Liechtenstein’s German. The corpus-based analysis reveals the juridical-semantic differences and the problematics of the verbal realization of the concepts. These hinder a proper interpretation and complicate the process of translation. The major solution is found through the specification of meaning by renaming. This solution may acquire the greatest importance in today’s world, because the process of globalization widens the area of utilization of the Treuhand and the Treuhänderschaft and any obscurity or incomprehensibility can cause problems during cross-national linguistic and juridical activities.